The Role Of BK In Supporting The Social Integration Of Individuals Of Special Populations In The Educational Environment - nurzainaulia; windywitria; gusmanlesmana (Indonesian Journal of Communication and Social, 2026)
Inclusive education requires a comprehensive support system for students with special needs, including tailored and collaborative guidance and support services. The aim of this article is to critically analyse the role of guidance and support in promoting social inclusion and the optimal development of students with special needs in inclusive schools. Based on a systematic literature review of recent studies, this article identifies four main dimensions of the role of counselling and support: (1) the management and implementation of needs-oriented counselling and support programmes; (2) group counselling techniques to develop students' social competencies; (3) the cooperative role of counsellors with teachers, parents, and other educational staff; (4) Strengthening students' resilience through counsellor support. Research findings indicate that the effectiveness of guidance and support services depends heavily on counsellors' competence in understanding the characteristics of children with special needs, their ability to adapt their guidance approaches, and the strength of interprofessional collaborative networks within the school environment. Meaningful social inclusion for children with special needs cannot be achieved solely through physical integration into mainstream classes, but requires planned interventions that actively involve school counsellors. This article recommends the development of an inclusive counselling and support model integrated into the school curriculum and programmes, as well as the strengthening of school counsellors' competencies through competency-based training in the field of inclusion.